(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
In the context of climate change litigation, the ruling of the Court of Rome in the “Giudizio Universale” case stands in contrast to the jurisprudential trends observed in Europe and the rest of the world. This contribution outlines the critical aspects of the decision and the issues that emerged afterwards, with refer-ence to the determination of the remaining carbon budget, that is the share of net anthropogenic carbon dioxide emissions still available to Italy in order to remain within the parameters set by the Paris Agreement.